2020
DOI: 10.2147/idr.s261510
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Clinical Study on the Use of Intraventricular Polymyxin B Supplemented by Continuous External Ventricular Drainage in the Treatment of Drug-Resistant Gram-Negative Bacilli Intracranial Infection</p>

Abstract: Purpose: To investigate the clinical effect of ventricular polymyxin B supplemented by continuous external ventricular drainage in the treatment of intracranial infection with multidrug-resistant (MDR) or extensively drug-resistant (XDR) Gram-negative (G-) bacilli following neurosurgery. Patients and Methods: A retrospective analysis was performed on 28 patients who had G-bacilli intracranial infection following neurosurgery in our department between January 2017 and December 2019. The patients were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The DR-AB-infected CSF is turbid, contains floccules, and may even become purulent, blocking the drainage tube and increasing the risk of infection. The previous research of our research team showed that the extraventricular drainage tube may be more suitable for drainage of purulent cerebrospinal fluid due to its thicker tubing (24). Among the 21 patients in the present study, 1 patient had a lumber cistern drainage tube and 1 patient had a ventriculoperitoneal shunt upon admission.…”
Section: Discussionmentioning
confidence: 58%
“…The DR-AB-infected CSF is turbid, contains floccules, and may even become purulent, blocking the drainage tube and increasing the risk of infection. The previous research of our research team showed that the extraventricular drainage tube may be more suitable for drainage of purulent cerebrospinal fluid due to its thicker tubing (24). Among the 21 patients in the present study, 1 patient had a lumber cistern drainage tube and 1 patient had a ventriculoperitoneal shunt upon admission.…”
Section: Discussionmentioning
confidence: 58%
“…Using the definition from Kidney Disease Improving Global Outcomes (KDIGO) guidelines ( 22 ), no cases of AKI were observed in the current study. Furthermore, the incidence and severity of nephrotoxicity was reported to be rare and mild in other studies ( 7 , 16 ). This suggests the dosage of combined administration of polymyxin B in the present study was comparatively safe for renal function.…”
Section: Discussionmentioning
confidence: 77%
“…Most of the identified papers/studies were case reports, including infants and pediatric patients. Chen et al ( 16 ) reported a total of 28 patients with MDR/XDR Gram-negative bacilli intracranial infection after neurosurgery. IVT polymyxin B at a dose of 5 mg/day was used for 14.96 ± 4.28 days (range, 9–23 days) and the clinical cure rate was 82.1% (23/28).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, drugs with inability to adequately permeate through the BBB (including amikacin, polymyxin B) are clinically used for intrathecal therapy of CNS infections caused by MDR Gram-negative pathogens ( Tunkel et al, 2017 ; Molinaro et al, 2018 ; Nau et al, 2020 ). Intrathecal/intraventricular polymyxins combined with systemic administration were recommended to treat intracranial infection caused by CRE in recent several studies ( Chen et al, 2020 ; Zhong et al, 2020 ). However, nephrotoxicity and neurotoxicity remain major problems for the clinical use of polymyxins.…”
Section: Discussionmentioning
confidence: 99%